2002
DOI: 10.2337/diabetes.51.3.871
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between TaqIB Cholesteryl Ester Transfer Protein Gene Polymorphism and Macrovascular Complications in Japanese Patients With Type 2 Diabetes

Abstract: Cholesteryl ester transfer protein (CETP) is a key regulating factor of lipid metabolism, and the polymorphism of its gene may therefore be a candidate for modulating the lipid parameters, altering the susceptibility to atherosclerosis in type 2 diabetic subjects. In a group of 443 unrelated Japanese patients with type 2 diabetes, we studied the B1B2 polymorphism at the CETP locus, which is detectable with the restriction enzyme TaqI. Patients were separated into three groups according to genotype and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 24 publications
3
27
0
Order By: Relevance
“…Some population-based studies have examined the relationship between TaqIB polymorphism and the risk of CAD in diabetic patients, but the reported results have been inconsistent (19,25,29). For example, two previous studies reported a relationship between TaqIB polymorphism and macrovascular complications of diabetes (29,35), while according to Chaaba (36), there is no correlation between this polymorphism and CAD in type 2 diabetic patients, which is in line with our study. It is still unknown how CETP isoforms could lead to the development of CAD in diabetic individuals.…”
Section: Acknowledgementssupporting
confidence: 80%
“…Some population-based studies have examined the relationship between TaqIB polymorphism and the risk of CAD in diabetic patients, but the reported results have been inconsistent (19,25,29). For example, two previous studies reported a relationship between TaqIB polymorphism and macrovascular complications of diabetes (29,35), while according to Chaaba (36), there is no correlation between this polymorphism and CAD in type 2 diabetic patients, which is in line with our study. It is still unknown how CETP isoforms could lead to the development of CAD in diabetic individuals.…”
Section: Acknowledgementssupporting
confidence: 80%
“…In type 2 diabetic patients, the B2 allele was associated in a dose-dependent fashion with higher HDL-C and lower CETP concentrations. Then, the prevalence of macrovascular complications was significantly higher in subjects with the B1B1 genotype (Kawasaki et al 2002). In Turkey, B1B1 genotype had higher in diabetic patients with myocardial infarction than diabetic patients without myocardial infarction (Yilmaz et al 2004).…”
Section: Discussionmentioning
confidence: 96%
“…The B1 allele is associated with low HDL-C levels and increased CETP levels and activity (Kuivenhoven et al 1997), whereas B2 allele is associated with a decreased risk of CVD (Ordovas et al 2000;Liu et al 2002) and MetS (Ozsait et al 2008). B1 allele has been shown to influence development of Alzheimer's disease and type 2 diabetes mellitus (Fidani et al 2004;Kawasaki et al 2002;Yilmaz et al 2004). Moreover, the association of B1 allele with MetS has been reported (Ozsait et al 2008;Sandhofer et al 2008;Elsammak et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the TaqIB genotype and the risk of CAD in diabetes has been investigated in some population-based studies, albeit without consistent results [26][27][28]. Two previous studies [26,27] revealed CETP TaqIB gene polymorphism to be associated with macrovascular complications of diabetes. However, Chaaba et al [28] reported that there was no association between CETP TaqIB gene polymorphism and CAD in type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 96%